Infinite Coordination Polymer Polydopamine Nanocomposites Dual‐Pathway Multistep Induction of Long‐Term Hyperimmunity Combined With Photothermal‐Chemo Synergistic Therapy Colorectal Cancer - Xiaojiang Zhang; Yujie Zhang; Pengqian Wang; Feiyu Shi; Siyuan Du; Zhe Zhang; Daocheng Wu; Junjun She; Ya Wang (Aggregate)
ABSTRACT To improve the long‐term therapeutic efficacy of colorectal cancer, we propose a synergistic treatment strategy involving dual‐pathway, multistep induction of long‐term hyperimmunity combined with photothermal‐chemotherapy. To implement this strategy, infinite coordination polymer nanoparticles (SN38‐Mn(II)‐EGCG ICP NPs) were prepared by coordinating SN38, EGCG, and Mn2+. These nanoparticles were then coated with polydopamine (PDA) and grafted with folate‐PEG‐thiol (FA‐PEG‐SH) onto their surfaces, producing tumor‐targeting folate‐modified PDA infinite coordination polymer nanocomposites (ICP@FA‐PDA nanocomposites). These nanocomposites exhibit a particle size of 94.9 ± 1.6 nm with a high drug loading capacity (83.3% ± 1.5%), drug release under acidic conditions while maintaining stability in physiological environments. Furthermore, each component within the nanocomposites serves multiple functions. Notably, the incorporation of multiple components triggers a powerful antitumor immune effect and establishes enduring immune memory through a dual‐pathway and multistep approach, which is produced with the activation of the cGAS‐STING pathway and immunogenic cell death (ICD) by a four‐component multistep process. Under a low‐dose regimen, this approach induces dual‐pathway hyperimmunity effect and generates ultra‐long immunological memory, marked by a ninefold increase in CD8+ T cell infiltration, a fourfold increase in CD4+ T lymphocytes, a fourfold reduction in Treg cells, and a fivefold increase in memory T cells. The remarkable therapy efficacy is achieved by hyperimmunity effect combination of SN38 and EGCG chemotherapy and photothermal therapy. In vivo studies demonstrated that mice treated with ICP@FA‐PDA nanocomposites achieved complete eradication of cancer within 21 days, with no recurrence observed within 60 days. These nanocomposites hold significant promise and potential for future clinical translation.